A Study on the Anatomy and Antibacterial Activity of Boesenbergia rotunda Rhizomes Against Staphylococcus aureus - Siti Mutripah; Lailatul Badriyah; Muhammad Haykal Putra; Nuradnin Hasan; Sarwoko Sarwoko; Bambang Purwoko (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2026)
Boesenbergia rotunda is a plant belonging to the Zingiberaceae family. This plant is known to contain various bioactive compounds with potential as natural antibacterial agents. This study aims to determine the microscopic anatomical characteristics, secondary metabolite content, and antibacterial activity of Boesenbergia rotunda rhizome extract against Staphylococcus aureus. The research methods used included microscopic observation, phytochemical screening, and antibacterial activity testing using the disk diffusion method. Anatomical observations revealed that the Boesenbergia rotunda rhizome consists of parenchyma tissue with starch granules scattered throughout the ground tissue. Phytochemical screening results indicated the presence of flavonoids, alkaloids, terpenoids, saponins, and tannins. Antibacterial activity testing showed that the Boesenbergia rotunda rhizome extract was able to inhibit the growth of Staphylococcus aureus, producing an inhibition zone with a diameter of ±17 mm. This inhibition zone diameter falls into the category of strong inhibition. This strong antibacterial activity is believed to result from the synergistic action of secondary metabolites that work through mechanisms of cell membrane damage, disruption of membrane permeability, and inhibition of bacterial cell wall synthesis. Based on the research results, the rhizome of Boesenbergia rotunda has the potential to be developed as a natural antibacterial source derived from herbal materials.